2022
DOI: 10.1002/ajs4.241
|View full text |Cite
|
Sign up to set email alerts
|

‘That's the bloodline’: Does Kinship and care translate to Kinship care?

Abstract: Kinship for First Nations people is a fundamental, yet complex, element of one's culture, enabling both belonging and relationality, and extending beyond blood family and relations. Kinship is also recognized as important within out‐of‐home care (OOHC) systems, with kinship care being the predominant OOHC placement type in Australia (AIHW, 2021). However, when First Nations children and young people are removed by the state, and placed into OOHC, it is important to interrogate whether kinship placements enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The increasing overrepresentation of Aboriginal and Torres Strait Islander children in OOHC, where placement may be away from their Indigenous families (AIHW, 2022; Liddle et al, 2022), poses a threat to cultural connection. Although kinship care is the most common form of OOHC placement, kinship care includes placement with non‐Indigenous family members (AIHW, 2021; Beaufils, 2022). In this research, all young people interviewed who lived in kinship care were placed with non‐Indigenous kinship carers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing overrepresentation of Aboriginal and Torres Strait Islander children in OOHC, where placement may be away from their Indigenous families (AIHW, 2022; Liddle et al, 2022), poses a threat to cultural connection. Although kinship care is the most common form of OOHC placement, kinship care includes placement with non‐Indigenous family members (AIHW, 2021; Beaufils, 2022). In this research, all young people interviewed who lived in kinship care were placed with non‐Indigenous kinship carers.…”
Section: Discussionmentioning
confidence: 99%
“…'Deep culture' is learned via immersion in a particular cultural milieu, where children learn complex aspects of culture, such as Aboriginal relationality (see Graham, 2014) (AIHW, 2021;Beaufils, 2022). In this research, all young people interviewed who lived in kinship care were placed with non-Indigenous kinship carers.…”
Section: Engagement With Surface Culturementioning
confidence: 99%
“…This approach does not suit some research contexts, as it infers that an objective reality can be drawn from qualitative data, ignoring the historical, social and situational conditions in which the research is located in (such as may be identified within a literature review), and similarly ignoring the role of the researcher/researchers and their influence on the research (Charmaz, 2017). CGT (and grounded theory more broadly) has been utilised within several Indigenous research contexts and in conjunction with Indigenous research methodologies (Bainbridge et al, 2013;Beaufils, 2022;Quinn, 2022;Wilson et al, 2022). CGT is utilised to coconstruct a theory with participants through their data, whilst still acknowledging that the development of the research and the undertaking of the analysis is still carried out by the researcher (who is informed by their own perspectives and biases; Charmaz, 2006;Chun Tie et al, 2019;Metelski et al, 2021).…”
Section: Et Hodmentioning
confidence: 99%
“…Indigenous children are 12 times more likely to be in out-of-home care than non-Indigenous children [3]. A key concern for Aboriginal communities is the frequency with which Aboriginal children are placed in non-Aboriginal protective care arrangements designated as kinship care that are not consistent with Aboriginal understandings of kin, and the attendant risk of children's alienation from family and culture [4].…”
Section: Formal Kinship Care-a Dominant Narrativementioning
confidence: 99%